Modelling and analysis of a combined electronic and micro-mechanical system - Atanasijević-Kunc, Maja (Strojniški vestnik, 2008)
The modelling of micro-mechanical systems in combination with integrated electronic circuits is a complex task demanding a knowledge of mechanical and microelectronic design in combination with system-modelling expertise, especially in cases where new possibilities regarding system construction and its properties are taken into account. Such modelling is becoming increasingly important because of the rapid growth of so-called "smart sensor" applications based on micro-mechanical devices. Our task was to create a reliable model of a micro-mechanical acceleration sensor that uses an extremely small and easy-to-produce mechanical system. The suspended mass and the output signal of this sensor are one order of magnitude smaller than existing systems. The described model was used for the further development of the mechanical and electrical parts of the system. The modelling inputs were the measurement data of the prototype devices, comprising the static characteristics of the device and the system responses to step-function excitation. Together with known physical properties and basic theoretical equations these data enabled us to create the described model, which showed good agreement with the measurement results.
Keywords: mikromehanika; modeliranje; senzorji; pospešek; kontrolni sistemi